Designing ecology. The organic as a possible paradigm of a sustainable and resilient architecture - Beatrice Balducci; Francesco Camilli (Agathón)
The integration of the organic dimension can be a strategy to reduce the impact of architecture on the environment and appears relevant to addressing the climate crisis. Positioning in a wider discussion on the relationship between man and nature, the paper shows how it is possible to broaden the understanding of the ecology of architecture, on the one hand, by looking at how some vernacular building techniques establish a relationship with living organic materials, on the other hand, through advanced architectural experiments that investigate the inhomogeneous nature of wood in order to integrate it into the project. The goal is to propose the inclusion of the organic dimension in architecture not only as a material issue but as a cultural paradigm shift where the building, rather than as an inert artefact, is interpreted as a piece of a broader and more complex ecology.